Spiritual well-being of INSTED, IIUM Students’ and Its relationship with college adjustment - Mansor, Norwati; Khalid, Nur Syahidah (2012)
This study attempts to discover spiritual well-being of INSTED, IIUM students and its relationship between spiritual well-being and college adjustment among them. It tries to determine whether spiritual well being is related to his college adjustment in order to attain good academic achievement. This study employed quantitave method. Sample were derived from three fields of study in Insitute of Education IIUM namely; Guidance and counseling, Teacher English as a second Language and Islamic Education students’. The researcher used descriptive statistics, Pearson correlation and ANOVA to analyzed the data.The findings of this study will benefit parents, counselors, teachers and policy maker.